2017
DOI: 10.5194/acp-2017-35
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaporating brine from frost flowers with electron microscopy, and implications for atmospheric chemistry and sea-salt aerosol formation

Abstract: <p><strong>Abstract.</strong> An environmental scanning electron microscope was used for the first time to obtain well-resolved images, in both temporal and spatial dimensions, of lab-prepared frost flowers (FFs) under evaporation within the chamber temperature range from −5 °C to −18 °C and pressures above 500 Pa. Our scanning shows temperature-dependent NaCl speciation: th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…Observations of negative nss‐SO 4 have been largely restricted to Antarctica, where relative contributions of anthropogenic sulfate can be very low and large areas of ocean are refrozen each year (Rankin & Wolff, ; Rankin et al, ). However, the potential for aerosol to be generated from frost flowers has been questioned in field and laboratory studies where frost flowers were not observed to produce aerosol even at relatively high wind speeds (Roscoe et al, ; Yang et al, ). Second, aerosol formation from blowing snow could also explain ambient sea salt seasonality and composition, though there are no observations to validate this hypothesis in the Arctic (J. Huang & Jaegle, ; Yang et al, ).…”
Section: Regional Arctic Processesmentioning
confidence: 99%
“…Observations of negative nss‐SO 4 have been largely restricted to Antarctica, where relative contributions of anthropogenic sulfate can be very low and large areas of ocean are refrozen each year (Rankin & Wolff, ; Rankin et al, ). However, the potential for aerosol to be generated from frost flowers has been questioned in field and laboratory studies where frost flowers were not observed to produce aerosol even at relatively high wind speeds (Roscoe et al, ; Yang et al, ). Second, aerosol formation from blowing snow could also explain ambient sea salt seasonality and composition, though there are no observations to validate this hypothesis in the Arctic (J. Huang & Jaegle, ; Yang et al, ).…”
Section: Regional Arctic Processesmentioning
confidence: 99%
“…These concave features are especially well imaged next to bare surface areas, similar to our findings for sublimation of isolated crystals. In the final stages of sublimation, where the substrate exerts some influence on the ice morphology, the features meet in sharp ridges and tips/asperities, with radii down to the nanometre range (similar to the features at evaporating brine; Yang et al, 2017). The interaction with the solid substrate has some stabilizing effect on these features, which could be mechanical (immobilization), but also thermal (good heat conduction against beam damage).…”
Section: Sublimation Of Ice Filmsmentioning
confidence: 99%
“…Dry deposition of SSA over land accounting for particles growth under high humidity conditions follows the sizesegregated scheme described in Zhang et al (2001). The dry deposition velocity over the ocean is calculated based on the Slinn and Slinn (1980) deposition model for natural waters.…”
Section: The Geos-chem Chemical Transport Modelmentioning
confidence: 99%